Model Pertuturan Anak Down Syndrome SMA Luar Biasa Dian Grahita Jakarta: Kajian Pragmatik - Wini Tarmini; Abd. Rahman A. Ghani; Martini Arelina Nike Pangaribuan (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This study aimed to identify and describe the speech model for children with down syndrome in Dian Grahita Special High School Jakarta with a pragmatic study. This research is qualitative. The subjects in this study were Dian Grahita Special High School students in Central Jakarta. The results of the research include: (a) representative speech by stating, agreeing, mentioning, showing, admitting, reporting; (b) commissive speech to agree, threatening: (c) directive speech ordering, inviting, warning, requesting, ordering; (d) expressive speech to criticize, apologize, complaining, thanking; and (e) declarative speech to prohibit. According to Searle, this study found 55 groups of speech acts with 87 variants of speech acts from the five major groups of speech acts. The percentage of speech acts data for children with Down syndrome is as follows. Representative utterances are 54 utterances or equivalent to 62%, commissive utterances are 4 utterances or equivalent to 5%, directive utterances are 21 utterances or equivalent to 24%, expressive utterances are 7 utterances or equivalent to 8%, and declarative utterances are 1 utterance or the equivalent of 1%. Students understand the communication conveyed by the teacher in classroom learning even though they express it only with short answers, including lingual markers, yes, no, okay, sorry, beware, already, not yet.